Test-retest reliability of the Nordic Musculoskeletal questionnaire (NMQ) in Vietnamese physical therapists - Thao, Le Thi Thach (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
Background: The Nordic Musculoskeletal Questionnaire (NMQ) is one of the screening tools to assess pain or discomfort of musculoskeletal disorders. It is widely used in various occupational populations. Many previous studies investigated the reliability of the NMQ, but there are no evidences in Vietnam. Objective: This study evaluated the test-retest reliability of the question about trouble with the locomotive organs in the NMQ in Vietnamese physical therapists (VPTs). Materials and method: It was a cross-sectional study in 10 VPTs by a convenient sampling technique. An online questionnaire was distributed to all participants twice times with a 7-day interval. They reported their musculoskeletal disorders during the last 12 months and the last 7 days and been prevented from doing normal work because of their troubles. The test-retest reliability of dichotomous data produced by the NMQ was accessed by using the kappa coefficient (k) and the level of significance was set at a p-value of less than 0.05. Results: Among 27 binary choice items, there were 5 items where k could not be computed as response were 100% negative on both testing occasions. Eight items showed not significant correlation poor to moderate agreement (k ≤ 0.40, p-value > 0.05). Fourteen items showed substantial to excellent test-retest reliability (k = 0.74-1.00, p-value < 0.05). Conclusion: The results suggest that the NMQ can be used with acceptable reliability for evaluating the musculoskeletal disorders and labour risks among VPTs.